Microscopic polyangiitis: an incidental finding in a patient with stroke - Abubakar Tauseef; Muhammad Sohaib Asghar; Mariam Amir; Maryam Zafar; Ayesha Anum; Haris Alvi; Mustafa Dawood; Uzma Rasheed; Mohammed Akram; Nisar Ahmed (Greater Baltimore Medical Center, 2020)
Microscopic polyangiitis (MPA) is a primary systemic vasculitis characterized by inflammation of small-sized vessels associated with the presence of anti-neutrophilic cytoplasmic antibodies. We report a case of a 39-year-old female diagnosed with microscopic polyangiitis as an incidental finding who presented with signs and symptoms of a stroke at a young age. Usually, it presents with fever, malaise, skin rash, weight loss, mononeuritis multiplex, and arthralgia/myalgia. Very rarely, it can involve meninges to cause meningeal vasculitis which can present as a febrile seizure. The most frequent neurological manifestation is peripheral neuropathy. Cerebral infarction or hemorrhage as an isolated finding is very rarely observed in the patient with MPA as was seen in our patient.